Spatial patterns of fungal endophytes in a subtropical montane rainforest of northern Taiwan. (June 2019) - Thomas, Daniel; Vandegrift, Roo; Roy, B.A.; Hsieh, Huei-Mei; Ju, Yu-Ming
Abstract: Fungal endophytes of plants are ubiquitous and important to host plant health. Wood-inhabiting and foliar endophyte communities from multiple tree hosts were sampled at multiple spatial scales across the Fushan forest dynamics plot in northern Taiwan, using culture-free, community DNA amplicon sequencing methods. Fungal endophyte communities were distinct between leaves and wood, but the mycobiomes were highly variable across and within tree species. Despite this, host tree species was an important predictor of mycobiome community-composition. Within a single common tree species, "core" mycobiomes were characterized using co-occurrence analysis. The spatial co-occurrence patterns of these few species of fungal endophytes appear to explain the strong host effect. For wood endophytes, a consistent core mycobiome coexisted with the host across the extent of the study. For leaf endophytes, the core fungi resembled a more dynamic, "gradient" model of the core microbiome, changing across the topography and distance of the study.